Eksegesis Efesus 5:16 dan Relevansinya terhadap Manajemen Waktu di Era Digital - Aliadi, Frans; Prissila, Amita (ICHTUS: Jurnal Teologi dan Pendidikan Kristiani, 2025)
This article is rooted in Paul's exhortation in Ephesians 5:16, "make the most of every opportunity, because the days are evil," which carries profound theological and ethical relevance for addressing the challenges of time management in the digital age. The background of this study arises from the widespread phenomenon of digital distraction among Christians, where technological advancements often lead to wasted time and a decline in spiritual quality of life. The purpose of this research is to analyze the meaning of "redeeming the time" in Ephesians 5:16 through biblical exegesis and contextual hermeneutics, and to explore its practical relevance for Christian time management today. This study employs a textual exegetical method, including linguistic analysis of key Greek terms in the original text, along with a contextual hermeneutical approach to relate the biblical message to the realities of the digital era. The findings indicate that “redeeming the time” demands a faith-driven awareness to wisely seize every kairos opportunity amid a world full of distractions. In conclusion, Ephesians 5:16 provides a strong theological foundation for Christians to manage their time proactively, productively, and in alignment with God’s will in the face of digital life challenges.